An Analysis of Etiological Factors and Pathogenesis of Ksheena Shukra in Male Infertility (AYUSHDHARA, 2025)
Infertility is characterized as the failure to conceive after 12 months of consistent unprotected sexual intercourse. Male infertility has emerged as a significant concern in contemporary society. The prevalence of this issue is increasing daily due to lifestyle changes. Factors contributing to male infertility encompass abnormal sperm production or function and/or difficulties in sperm delivery. Oligozoospermia refers to the male infertility condition identified by a low sperm concentration in the ejaculate. According to the World Health Organization (WHO), a low sperm count is defined as fewer than 20 million sperm per milliliter. A normal sperm count ranges from 20 to 150 million sperm per milliliter. Ayurveda has identified various terms associated with male infertility, including Ksheena shukra, Ksheena retasa, Alpa retasa, and Shukra dosha, which correspond to conditions linked with oligospermia. The current paper aims at putting forwards the etiopathogenesis of Ksheena shukra on the basis Ayurvedic concepts.